2009
DOI: 10.1002/glia.20855
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐4 orthogonal arrays of particles are the target for neuromyelitis optica autoantibodies

Abstract: Neuromyelitis optica (NMO) is an inflammatory autoimmune demyelinating disease of the central nervous system (CNS) which in autoantibodies produced by patients with NMO (NMO-IgG) recognize a glial water channel protein, Aquaporin-4 (AQP4) expressed as two major isoforms, M1- and M23-AQP4, in which the plasma membrane form orthogonal arrays of particles (OAPs). AQP4-M23 is the OAP-forming isoform, whereas AQP4-M1 alone is unable to form OAPs. The function of AQP4 organization into OAPs in normal physiology is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 147 publications
(167 citation statements)
references
References 42 publications
7
156
3
1
Order By: Relevance
“…Likewise, whole serum from a patient with NMO also stained both isoforms. This finding contradicts a recent study reporting exclusive staining of M23 by NMO-IgG (26). rAb-53 also stained AQP4 on the surface of primary glial cell cultures from mouse neonatal brain cortex (Fig.…”
Section: Diffusion Of Native Aqp4 In Primary Glial Cell Cultures Is Scontrasting
confidence: 98%
See 2 more Smart Citations
“…Likewise, whole serum from a patient with NMO also stained both isoforms. This finding contradicts a recent study reporting exclusive staining of M23 by NMO-IgG (26). rAb-53 also stained AQP4 on the surface of primary glial cell cultures from mouse neonatal brain cortex (Fig.…”
Section: Diffusion Of Native Aqp4 In Primary Glial Cell Cultures Is Scontrasting
confidence: 98%
“…The majority of NMO patients contain in their serum autoantibodies (NMO-IgG) recognizing AQP4 on the surface of glial cells (12). A recent study suggested that NMO-IgG specifically targets AQP4 OAPs, based on imaging data showing preferential staining of M23-transfected cells but not M1-transfected cells (26). This finding suggests that OAPs are the site of NMO pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that NMO patient serum and a recombinant monoclonal NMO-IgG were each able to bind to both the M23 and M1 isoforms of AQP4 (26), which contradicted an earlier study reporting undetectable binding to M1 AQP4 (28). Here, we used fluorescence ratio imaging to quantify the binding of NMO-IgG to AQP4 and to determine the role of AQP4 isoforms and OAPs in NMO-IgG binding.…”
Section: Discussionmentioning
confidence: 62%
“…A prior report that analyzed NMO sera concluded that OAPs are the exclusive target of NMO-IgG (28). However, this conclusion cannot be correct because the clinical serum assay for serum anti-AQP4 autoantibody uses M1 AQP4 (29), which does not form OAPs, and we (4,26) and others (30) reported strong binding of some NMO autoantibodies to cells expressing only M1 AQP4.…”
mentioning
confidence: 71%